Broadband, Spectrally Flat, Graphene‐based Terahertz Modulators. Issue 45 (8th October 2015) - Shi, Fenghua; Chen, Yihang; Han, Peng; Tassin, Philippe
Abstract : Advances in the efficient manipulation of terahertz waves are crucial for the further development of terahertz technology, promising applications in many diverse areas, such as biotechnology and spectroscopy, to name just a few. Due to its exceptional electronic and optical properties, graphene is a good candidate for terahertz electro‐absorption modulators. However, graphene‐based modulators demonstrated to date are limited in bandwidth due to Fabry–Perot oscillations in the modulators' substrate. Here, a novel method is demonstrated to design electrically controlled graphene‐based modulators that can achieve broadband and spectrally flat modulation of terahertz beams. In our design, a graphene layer is sandwiched between a dielectric and a slightly doped substrate on a metal reflector. It is shown that the spectral dependence of the electric field intensity at the graphene layer can be dramatically modified by optimizing the structural parameters of the device. In this way, the electric field intensity can be spectrally flat and even compensate for the dispersion of the graphene conductivity, resulting in almost invariant absorption in a wide frequency range. Modulation depths up to 76% can be achieved within a fractional operational bandwidth of over 55%. It is expected that our modulator designs will enable the use of terahertz technology in applications requiring broadband operation. Abstract : Broadband, spectrally flat graphene‐based terahertz modulation is realized by eliminating the effect from the spectral dispersion of the graphene conductivity and that from the Fabry–Perot oscillations in the supporting substrate. Modulation depths up to 76% are achieved within a fractional operational bandwidth of over 55%. The modulator designs here will enable the use of terahertz technology in applications requiring broadband operation.